The Influence Of Personalized Ads On E-Commerce Applications In Indonesia On User Satisfaction - Gevyo Irene (Publikasi Indonesia, 2023)
The rapid growth of technology and the internet has encouraged the development of the e-commerce industry in Indonesia. In an effort to increase sales and interaction with customers, e-commerce companies are increasingly adopting the use of ads tailored to individual preferences, known as personalized ads. This study aims to investigate the effect of personalized ads on e-commerce applications in Indonesia on user satisfaction. This study used quantitative research methods. The data collection technique carried out is to distribute questionnaires. The collected data is then statistically analyzed using SPSS. The results showed that personalized ads have a positive influence on the level of user satisfaction of e-commerce applications in Indonesia. Users who receive personalized ads are more satisfied with e-commerce apps than users who don't receive personalized ads.